If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 10 = -55 + -7x Reorder the terms: 10 + 6x = -55 + -7x Solving 10 + 6x = -55 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 10 + 6x + 7x = -55 + -7x + 7x Combine like terms: 6x + 7x = 13x 10 + 13x = -55 + -7x + 7x Combine like terms: -7x + 7x = 0 10 + 13x = -55 + 0 10 + 13x = -55 Add '-10' to each side of the equation. 10 + -10 + 13x = -55 + -10 Combine like terms: 10 + -10 = 0 0 + 13x = -55 + -10 13x = -55 + -10 Combine like terms: -55 + -10 = -65 13x = -65 Divide each side by '13'. x = -5 Simplifying x = -5
| 120-3x=5x+24 | | 5(c-8)-3(2c+12)=84 | | 3(+3)=21 | | 7n+9=8n+16 | | y^3+216=0 | | 4x-8x+58=5x+31 | | -13+37=-4(x+3) | | g+12+9g=0 | | 4+y/5=y | | 4x-7+12=6(2x+4) | | (8.54)(1-8.54)/100= | | 5y=12x+1 | | 5y-9=3(-1) | | 15+8x=8x+15 | | 2(3x-4)=6x+10 | | 6x^3-61x^2+10x=0 | | 9t^2-6t=ln(0) | | 131-2x=43x+21 | | 7-5x-5-5x=4 | | 7-5x-5-5x= | | 139-3x=24x+22 | | 9t^2-6t=0 | | 15+6n=4n+23 | | 5-7x=36-13x | | 2a*5=-6-6 | | 2+4x=2x+9 | | 6x+9=2x-15 | | -6-6=a | | -6-6=-6-6 | | 5y=3(0)-9 | | 4*(3x)+2*(24x)=144+4*(6x) | | -6-6=-12 |